Ni‐Ferrite an efficient catalyst for synthesis of 3‐aryl substituted isoxazole‐5‐carboxylic acids via one‐pot multicomponent reaction. (25th December 2022) - Totre, Ganesh; Shinde, Dnyaneshwar; Patil, Prakash; Kulkarni, Pramod
Abstract: Here, we have reported an efficient one‐pot, three‐component reaction between various aryl aldehydes, NH2 OH.HCl, and propargyl alcohol using Ni‐Fe2 O4 as a nanocatalyst. Reactions were performed in ethanol at room temperature to obtain various 3‐aryl substituted isoxazole‐5‐carboxylic acids. The advantage of this protocol is that it formed isoxazole derivatives with free carboxylic acid functionality in one pot, which could transform into various other functional groups. This approach has several merits, including a quick reaction time, a wide range of substrates, excellent product yields, and reusable catalysts. Abstract : Here we have developed one pot three component synthesis of 3‐aryl substituted isoxazole‐5‐carboxylic acid.